Lithium battery diaphragm and preparation method thereof

By using the coating structure of TiCx and wetting agent in the lithium-ion battery separator, the problem of insufficient wetting and thermal stability of traditional separators is solved, the ionic conductivity and thermal stability of lithium-ion batteries are improved, and the battery is enhanced Safety, especially in lithium-sulfur batteries, effectively inhibit the polysulfide shuttle effect.

CN119208905AActive Publication Date: 2024-12-27HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411501418.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-27
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators have poor wetting properties in lithium ion transmission and diffusion, and insufficient high-temperature thermal stability, resulting in limited battery performance and safety hazards. Especially in lithium-sulfur batteries, it is impossible to suppress the polysulfide shuttle effect.

Method used

Using a coating structure including dispersant, TiCx and wetting agent, TiCx is a non-stoichiometric compound, prepared by mechanical alloying process, combining materials such as polyacrylic acid and polyoxyethylene alkylphenol ether to form a high-performance membrane to enhance Ion permeability and thermal stability.

Benefits of technology

It significantly improves the ionic conductivity and thermal stability of lithium-ion batteries, reduces the internal resistance of the battery, enhances safety, avoids thermal runaway accidents, and effectively inhibits the polysulfide shuttle effect in lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208905A_ABST
    Figure CN119208905A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery diaphragm and a preparation method thereof, the lithium battery diaphragm comprises a base membrane and a coating on the base membrane, the coating comprises a dispersant, TiCx and a wetting agent, the TiCx is a non-stoichiometric ratio compound, the TiCx is prepared from TiC and Ti, and x is 0.25-0.5. A large number of C vacancies exist in the non-stoichiometric compound TiCx, and the dynamic diameter of the vacancies is larger than that of Li < + >, so that in the coating process, the C vacancies can provide channels for migration of Li < + >, the ionic conductivity of the diaphragm is greatly improved under the condition that other properties of the diaphragm are not affected, the internal resistance of a battery is reduced, and the service life of the battery is prolonged. The heat resistance of the diaphragm is improved while the thickness is guaranteed, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art

[0002] With the rapid development of modern industrial society, the reserves of non-renewable energy represented by coal, oil and natural gas are constantly decreasing, leading to the depletion of fossil energy and triggering a new energy crisis. At the same time, the extensive use of fossil fuels not only destroys the ecological environment of the earth, but also aggravates the greenhouse effect and causes global warming. Therefore, the development of new renewable clean energy has become the top priority of countries around the world in the process of development. Renewable energy represented by wind energy, solar energy and tidal energy is expected to replace traditional fossil energy and provide "power" for social development. However, since these clean energy sources are greatly affected by external factors such as geographical environment, they cannot meet the demand for energy storage systems in daily production and life. In recent years, with the rapid development of the electric vehicle and portable electronic device market, people's demand for high energy density, high power density and environmentally friendly energy storage conversion devices is increasing. Among many energy storage systems, electrochemical energy storage devices have attracted much attention as an efficient and economical energy storage method. Lithium-ion secondary batteries have dominated the energy storage system market due to their advantages such as high energy density, long cycle life, wide operating temperature range and no memory effect. At present, lithium-ion batteries have been widely used in 3C electronic products, hybrid / all-electric vehicles, drones, smart grids and other fields, greatly changing people's production and lifestyles.

[0003] The diaphragm is an important component of lithium-ion batteries. It can prevent direct contact between the positive and negative electrodes and promote the shuttling of lithium ions between the positive and negative electrodes. Traditional commercial polyolefin diaphragms have the advantages of low production cost, uniform pore structure, and excellent mechanical strength, and have always dominated the lithium battery diaphragm market. However, commercial polyolefin diaphragms also have many problems that cannot be ignored: (1) Poor wettability with electrolyte, which leads to the obstruction of lithium ion transmission and diffusion inside the diaphragm, thus affecting the performance of the battery; (2) Poor high-temperature thermal stability. When heated, the diaphragm will shrink severely, resulting in internal short circuits in the battery, thereby causing safety accidents such as thermal runaway; (3) In lithium-sulfur batteries, due to the large pore size and simple structure of the diaphragm, it is impossible to inhibit the shuttling effect of polysulfides. Although the diaphragm does not directly participate in the electrochemical reaction, its properties determine the electrochemical performance and safety performance of the lithium-ion battery. The diaphragm should have a high porosity and electrolyte absorption rate so that lithium ions can be transferred quickly. In addition, it should have excellent thermal stability, and the separator should be able to maintain its structural integrity when lithium dendrites penetrate to prevent internal short circuits. To this end, a high-performance material is needed that has good ion permeability and high-temperature thermal stability while ensuring the mechanical strength and electronic insulation of the separator. Summary of the invention

[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium battery separator.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned lithium battery separator.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A lithium battery separator, comprising: a base film and a coating on the base film, wherein the coating comprises: a dispersant, TiC x and wetting agent, by mass, dispersant, TiC x The ratio of TiC to wetting agent is (0.1-0.5): (15-20): (0.03-0.1), among which TiC x It is a non-stoichiometric compound, TiC x , x=0.25~0.5.

[0008] In the above technical solution, the dispersant is one or a mixture of two of polyacrylic acid and polyvinyl ether.

[0009] In the above technical solution, the wetting agent is one or a mixture of two of polyoxyethylene alkylphenol ether, sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.

[0010] In the above technical solution, TiC is prepared x The method is as follows: mixing powder and powder dispersion control agent, ball milling to uniformity, sealing, mechanical alloying, and obtaining TiC x The powder materials are titanium carbide (TiC) powder and titanium (Ti) powder. Calculated by the amount of substance, the ratio of titanium carbide powder to titanium powder is 1: (1-3).

[0011] In the preparation of TiC x In the method, the powder dispersion control agent is ethanol, and the powder dispersion control agent is used to inhibit the agglomeration of the powder during the ball milling process.

[0012] In the preparation of TiC x In the method, the ratio of powder to powder dispersion control agent is (30-70):1 by weight.

[0013] In the preparation of TiC x The method comprises the following steps: mixing titanium carbide (TiC) powder and titanium (Ti) powder, placing in a cemented carbide ball, dropping a powder dispersion control agent, mixing uniformly, sealing, and mechanically alloying at a speed of 400 to 600 r / min for 50 to 80 h at room temperature, in an inert gas or nitrogen atmosphere to obtain TiC. x .

[0014] In the above technical solution, mechanical alloying is carried out at room temperature at a rotation speed of 400-600 r / min for 50-80 hours, wherein the machine is stopped for 30 minutes every 2 hours (for heat dissipation) and the material is pounded once every 30 hours.

[0015] In the above technical solution, the ratio of cemented carbide balls to powder is (15-25):1 by mass.

[0016] In the above technical solution, the diameters of the cemented carbide balls are 8 mm, 5 mm and 2 mm respectively, and the ratio of the cemented carbide balls with diameters of 8 mm, 5 mm and 2 mm is 6:3:1 in terms of mass fraction.

[0017] The preparation method of the above-mentioned lithium battery separator comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the lithium battery separator.

[0018] In the above technical solution, the coating speed is 10 to 20 m / min.

[0019] In the above technical solution, the base film is made of polyethylene or polypropylene.

[0020] In the above technical solution, the thickness of the coating is 1 to 5 μm.

[0021] A slurry comprising: a dispersant, water, TiC x , pore formers, thickeners, adhesives and wetting agents, by weight, dispersants, water, TiC x , pore-forming agent, thickener, adhesive and wetting agent ratio is (0.1~0.5):(23~30):(15~20):(1.5~2.5):(2~5):(1.3~3):(0.03~0.1).

[0022] In the above technical solution, the thickener is one or a mixture of carboxymethyl cellulose and sodium carboxymethyl cellulose.

[0023] In the above technical solution, the adhesive is one or a mixture of several of acrylate, epoxy resin, phenolic resin and polyurethane.

[0024] The method for preparing the slurry comprises: dispersing agent, water, TiC x , pore former, thickener, adhesive and wetting agent are mixed until uniform to obtain slurry.

[0025] In the above technical solution, the pore-forming agent is one of ammonium bicarbonate and isopropanol.

[0026] In the above technical solution, the method for preparing the slurry comprises the following steps:

[0027] Step 1: Dispersant, water and TiC x Mixing until uniform to obtain a first substance;

[0028] In step 1, dispersant, water and TiC x The mixture is mixed, stirred at room temperature at a rotation speed of 1500 to 2500 r / min and a revolution speed of 30 to 50 r / min for 20 to 30 min, and sand-milled for at least 5 min until uniform, to obtain the first substance.

[0029] Step 2, mixing the first substance and the pore-forming agent until uniformly, to obtain the second substance, mixing the second substance and the thickener until uniformly, to obtain the third substance, mixing the third substance, the adhesive and the wetting agent until uniformly, to obtain the slurry.

[0030] In step 2, the first substance and the pore-forming agent are mixed and stirred for 10 to 20 minutes until they are uniform, thereby obtaining a second substance.

[0031] In step 2, the second substance and the thickener are mixed and stirred for 10 to 20 minutes until they are uniform, thereby obtaining a third substance.

[0032] In step 2, the third substance, the adhesive and the wetting agent are mixed and stirred for 10 to 20 minutes until they are uniform to obtain a slurry.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The non-stoichiometric compound TiC of the present invention x There are a large number of C vacancies in the + The kinetic diameter of the carbon vacancies can be used as Li + It provides a channel for the migration of ions, greatly improves the ionic conductivity of the diaphragm without affecting other properties of the diaphragm, reduces the internal resistance of the battery, improves the heat resistance of the diaphragm while ensuring the thickness, and improves the safety of the battery;

[0035] 2.TiC x It has excellent mechanical properties and can be used as a rigid ceramic support skeleton to improve the thermal shrinkage, high temperature stability and insulation performance of polyolefin separators to ensure that the battery is not punctured;

[0036] 3. TiC prepared by the present invention x High purity, low content of magnetic substances and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 TiC x XRD pattern of

[0038] Figure 2TiC x SEM image of . DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0040] In the following examples, the base film is a polyethylene base film.

[0041] In the following embodiments, the speed ratio of the anilox roller is 140%.

[0042] Ionic conductivity: Temperature: room temperature 25±5℃; Relative humidity: 40~50%.

[0043] Liquid absorption and retention rate: Cut the diaphragm into 50mm*50mm samples. For diaphragms with a width less than 50mm, cut the full-width diaphragm with a length of 50mm, and the side length is accurate to 1mm. Weigh the cut samples and record them as m1 (accurate to 0.01mg). Soak the weighed diaphragm in the electrolyte, soak it at room temperature for (30±1) minutes, take it out, wipe the free electrolyte on the surface of the diaphragm until the granular electrolyte is no longer visible to the naked eye, weigh it, and record it as m2 (accurate to 0.01mg). Then put it aside for one hour, weigh it, and record it as m3 (accurate to 0.01mg). At least 3 sets of data should be tested for each sample. The diaphragm liquid absorption rate and liquid retention rate are measured in mass fraction, and the value is expressed in %, and calculated according to the following formula:

[0044] Liquid absorption rate EU (%) = (m2-m1) / m1*100%

[0045] Liquid retention rate EU1 (%) = (m3-m1) / m1*100%

[0046] Where:

[0047] m1——unit is milligram (mg);

[0048] m2——unit: milligram (mg);

[0049] m3——unit: milligram (mg).

[0050] The average of the three sets of data was calculated, and the result was retained to two decimal places. The separator was one of the lithium battery separators of Examples 4 to 6 and Comparative Examples 3 to 6.

[0051] Examples 1 to 3

[0052] A method for preparing a slurry comprises the following steps:

[0053] Step 1: Dispersant, water and non-stoichiometric compound (TiC x) were mixed and stirred at room temperature at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for A min to make TiC x Disperse evenly in water and grind with a sand mill for 5 minutes until uniform to obtain the first substance (TiC x Dispersion), the dispersant is polyacrylic acid;

[0054] Step 2: Mix the first substance and the pore former, stir for 10 minutes until uniform, to obtain the second substance; mix the second substance and the thickener, stir for 10 minutes until uniform, to obtain the third substance; mix the third substance, the adhesive and the wetting agent, stir for 10 minutes until uniform, to obtain a slurry; and the dispersant, water, TiC x The ratio of pore-forming agent, thickener, adhesive and wetting agent is B, the pore-forming agent is isopropyl alcohol, the thickener is carboxymethyl cellulose, the adhesive is acrylate, and the wetting agent is polyoxyethylene alkylphenol ether.

[0055] Preparation of TiC x The method is as follows: powders (titanium carbide (TiC) powder and titanium (Ti) powder) are loaded into a ball mill (hard alloy mill), hard alloy balls are placed, a powder dispersion control agent is added dropwise, the mixture is uniformly mixed (hand mixing for 10 minutes), the mixture is sealed, the ball mill is placed on a planetary ball mill, and mechanical alloying is performed at room temperature and nitrogen atmosphere at a speed of 400 r / min for 60 hours (the machine is stopped for 30 minutes every 2 hours (heat dissipation), and the material is pounded once every 30 hours of mechanical alloying) to obtain TiC x , by mass fraction, the ratio of titanium carbide powder to titanium powder is C, the value of "x" is D, wherein the powder dispersion control agent is ethanol (used to inhibit the agglomeration of powder during ball milling). By mass fraction, the ratio of powder to powder dispersion control agent is 50:1, by mass fraction, the ratio of cemented carbide ball to powder is 20:1, the cemented carbide balls are spheres with diameters of 8mm, 5mm and 2mm, respectively, and by mass fraction, the ratio of cemented carbide balls with diameters of 8mm, 5mm and 2mm is 6:3:1. The values ​​of A, B, C and D are shown in Table 1.

[0056] Table 1

[0057] Example A(min) B C D Example 1 30 0.2:25.2:17.5:1.95:3.5:1.6:0.05 2:3 0.4 Example 2 25 0.3:25.74:16:2.5:3:2:0.04 2:3 0.4 Example 3 30 0.2:25.2:17.5:1.95:3.5:1.6:0.05 1:3 0.25

[0058] Comparative Example 1

[0059] A method for preparing slurry is basically the same as that in Example 1, except that: x ” is replaced by “alumina powder”.

[0060] Comparative Example 2

[0061] A method for preparing slurry is basically the same as that of Example 2, except that: x ” is replaced by “alumina powder”.

[0062] Examples 4 to 6 and Comparative Examples 3 to 4

[0063] A method for preparing a lithium battery separator comprises: placing a base film on a coating machine equipped with slurry (the unwinding tension of the coating machine is 32N, and the winding tension is 4N), coating the slurry on one side of the base film at a coating speed of Xm / min, and pulling the base film into a drying device through a traction roller and drying it at 65°C for 2min, obtaining a coating with a thickness of Yμm on the base film, and obtaining a lithium battery separator. The slurry is one of the slurries prepared in Examples 1 to 3 and Comparative Examples 1 to 2. The specification of the base film is Z1, and the specification of the anilox roller is Z2.

[0064] X, Y, Z1 and Z2 are shown in Table 2.

[0065] Table 2

[0066]

[0067] Comparative Example 5

[0068] A method for preparing a lithium battery separator is substantially the same as that of Comparative Example 3, except that the base film and the anilox roller used are different. The base film in Comparative Example 5 has a size of 1000 mm × 7 μm, and the anilox roller has a size of 1150 mm × 100 mm × 2 μm (the coating thickness of the lithium battery separator in Comparative Example 5 is 2 μm).

[0069] Comparative Example 6

[0070] A wrinkled MXene modified separator for a lithium-ion battery, which is Example 1 of the invention patent with publication number CN 114927830 A.

[0071] The test data of the lithium battery separators of Examples 4 to 6, Comparative Examples 3 to 5, and the wrinkled MXene modified separator for lithium ion batteries of Comparative Example 6 are shown in Table 3.

[0072] Table 3

[0073]

[0074] Figure 1 TiC x XRD pattern of Figure 1 It can be seen that in addition to a small amount of tungsten carbide (from the ball mill and cemented carbide balls), there is no other phase in the XRD graph. xThe high purity and low content of magnetic substances indicate that the Ti in the raw material reacts completely with the C element in TiC, or that the C atoms diffuse into the Ti lattice during the ball milling process, causing the crystal structure of the low-temperature hexagonal Ti to change and finally exist in the form of a face-centered cubic structure of TiC. The two phases are synthesized into a single stable phase. And the prepared TiC is obtained by calculation. x The lattice constant is The lattice constant of TiC is TiC x The lattice constant of TiC is smaller than that of TiC because of the above reaction. Ti atoms enter the TiC lattice during the ball milling process, resulting in lattice distortion. A large number of C vacancies promote TiC x The lattice constant becomes smaller.

[0075] Figure 2 TiC x SEM image of Figure 2 It can be seen that TiC x The particles are spherical, with a size of about 0.1-0.2μm, and the particle size distribution is relatively uniform, which is beneficial to TiC x Dispersion and coating in slurry. x It achieves overall densification through its own accumulation, serving as both a ceramic skeleton reinforcement phase of the diaphragm and an ion conducting phase, which helps to improve the comprehensive performance of the diaphragm.

[0076] Comparative Example 7

[0077] A high-strength and tough layered structure TiC x / Ti-based composite material, which is Example 1 of the invention patent with publication number CN 118082355 A.

[0078] The material prepared by the invention patent with publication number CN 118082355 A contains metal impurities and has too high electronic conductivity. It will leak electricity when used to prepare lithium battery separators and cannot be used in actual production.

[0079] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A lithium battery separator, characterized in that: include: Base film and coating on the base film, the coating includes: dispersant, TiC x and wetting agent, by mass, dispersant, TiC x The ratio of TiC to wetting agent is (0.1-0.5): (15-20): (0.03-0.1), among which TiC x It is a non-stoichiometric compound, x=0.25~0.

5.

2. The lithium battery separator according to claim 1, characterized in that Preparation of TiC x The method is as follows: mixing powder and powder dispersion control agent, ball milling to uniformity, sealing, mechanical alloying, and obtaining TiC x The powder materials are titanium carbide powder and titanium powder. The ratio of titanium carbide powder to titanium powder is 1:(1-3) based on the amount of substance.

3. The lithium battery separator according to claim 2, characterized in that: The powder dispersion control agent is ethanol, and the powder dispersion control agent is used to inhibit the agglomeration of powders during the ball milling process.

4. The lithium battery separator according to claim 3, characterized in that: Calculated by weight, the ratio of powder to powder dispersion control agent is (30-70):

1.

5. The lithium battery separator according to claim 4, characterized in that: Mix titanium carbide powder and titanium powder, put them into cemented carbide balls, add powder dispersion control agent, mix them evenly, seal them, and mechanically alloy them at room temperature in an inert gas or nitrogen atmosphere for 50 to 80 hours to obtain TiC x .

6. The method for preparing a lithium battery separator according to any one of claims 1 to 5, characterized in that: The method comprises: coating the slurry on a base film, drying, obtaining a coating on the base film, and obtaining a lithium battery separator.

7. A slurry, characterized in that: include: Dispersant, water, TiC x , pore formers, thickeners, adhesives and wetting agents, by weight, dispersants, water, TiC x , pore-forming agent, thickener, adhesive and wetting agent ratio is (0.1~0.5):(23~30):(15~20):(1.5~2.5):(2~5):(1.3~3):(0.03~0.1).

8. The method for preparing the slurry according to claim 7, characterized in that: include: Dispersant, water, TiC x , pore former, thickener, adhesive and wetting agent are mixed until uniform to obtain slurry. 9.TiC x Application in improving the ionic conductivity of membranes. 10.TiC x Used to improve the heat resistance, liquid absorption rate, liquid retention rate and breakdown voltage of the diaphragm.

Citation Information

Patent Citations

  • Modified diaphragm and preparation method and application therefor

    CN105679983A

  • Silicon carbide composite material and preparation method thereof

    CN109627010A

  • Preparation method of lithium ion battery separator

    CN109638203A

  • Heat-conducting and electric-conducting material coated diaphragm and preparation method thereof

    CN112787034A